Diesel fuel and passenger cars receive preferential tax treatment in Europe: Reform of taxation needed in Germany - Uwe Kunert (DIW Weekly Report, 2018)
Duties and taxes on cars are an important source of revenue for European governments and the tax systems are also designed with the goal of achieving environmental policy objectives. A systematic and quantitative comparison of passenger car taxation in 30 European countries shows significant differences among them. However, in almost every country, the use of vehicles with diesel engines is taxed less than that of cars with gasoline engines, and the share of fixed charges (on acquisition, registration, and ownership) is higher than the share of use-related levies. Germany has shifted its position with regard to both types of tax and now ranks low in terms of the overall tax burden. However, the German motor vehicle tax is neither fiscally profitable nor does it have the desired effect. Energy tax rates have remained the same since 2003 and its real value has declined by a fifth in real terms. With this in mind, both types of taxes are in need of reform and increasing the diesel tax should be a priority.
Keywords: H23; O38; Q52; R48; 330; environmental taxes; technological change; government policy; transportation; regulatory policies